The Effect Of Rhythmic Auditory Stimulation On Dynamic Balance Of Post-Stroke Patients At Cengkareng Regional Hospital - Basalamah, H.; Ali, Mohammad; Achwan, Achwan; Pambudi, Restu Arya (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Background: Balance disorders cause limitations in daily life activities after stroke, especially when moving from sitting to standing and walking. 83% of stroke patients in the acute phase experience balance disorders. The risk of falls increases by 73% in the 6 months after stroke. Rhythmic auditory stimulation (RAS) is a neuro-rehabilitation process that involves repetitive movements with rhythmic patterns which is very effective in teaching post-stroke patients how to balance when walking. Purpose: To determine the effect of giving Rhythmic auditory stimulation on dynamic balance after stroke at Cengkareng Regional Hospital. Method: This research used pre-experimental with one group pre-posttest. This research was carried out 3 times a week for 4 weeks. This research sample consisted of 12 people. Dynamic balance was measured using the Time Up & Go Test (TUGT) before and after intervention. Results: The paired sample t-test on dynamic balance before and after the intervention obtained a p-value of 0.002 (p-value <0.05). Conclusion: There is an effect of rhythmic auditory stimulation on dynamic balance after stroke at Cengkareng Regional Hospital